The Impact of Information Quality, Trust, Anxiety, and Health Consciousness on Intention to Buy Health Supplements in The Post Pandemic Era - Purnama Dewi Pata; Bernard Alfa E. Manurung; Edwin Hari Wardhana; Maria Christiane Budiman; Nataliawati Nataliawati (Syntax Idea)
The purpose of this study is to analyze the factors affecting consumer’s intention to buy health supplements using the expanding theory of planned behavior model. The variables of perceived information quality, trust, anxiety, health consciousness are integrated in the model of this study. A total of 333 valid questionnaire responses were collected via an online survey, from respondents living in Jakarta and suburb (Jabodetabek) area, Indonesia. The findings indicate that perceived information quality influences trust, anxiety, and health consciousness. Moreover, both of trust and health consciousness influence customer’s attitude. Eventually, the customer’s attitude and subjective norms influence the intentions to buy health supplements. The authors used a sample based on Jabodetabek area that assume they have similar access to perceived information quality. The present study also has not considered educational and economic status of the respondents